New biological temporary skin cover Xe-Derma(®) in the treatment of superficial scald burns in children - Zajicek, Robert; Matouskova, Eva; Broz, Ludomir; Kubok, Richard; Waldauf, Petr; Königova, Radana (Burns, 2011)
BACKGROUND: Xe-Derma® is a new dry sterile biological cover derived from acellular pig dermis. Hydrated Xe-Derma® displays bio-mechanical features similar to the normal skin. The aim of the present study was to compare the efficacy of Xe-Derma® with hydrocolloid dressing Askina THINSite® for treatment of superficial burns in children in a prospective study. MATERIALS AND METHODS: In a prospective study, 86 patients (5 months to 7 years of age) with superficial scald burns on a surface area of 1-35% BSA were enrolled. In the course of the study, 43 patients were treated with Xe-Derma® and 43 patients with Askina THINSite®. We collected data including the percentage of BSA covered with biological or synthetic material, epithelization time, the number of complete conversions (deepening of 100% of covered area into deep dermal wound) under each cover, the number and extent of partial conversions (deepening of less then 100% of covered area into deep dermal wound), infectious complications, the number of reapplications of the temporary cover and the extent in square centimetres of dressing material needed for successful healing of 1% BSA. RESULTS: No significant difference in the epithelization time, percentage of conversion from superficial to deep dermal burns and percentage of infectious complication was detected between the two groups. However, patients in the Xe-Derma® group were burned on a more extensive burn surface area (p ≤ 0.028). Xe-Derma® showed adherence to the wound and therefore there has been no need to be changed The number of reapplications and therefore also the number of square centimetres needed for successful healing of 1% BSA were statistically higher in the Askina THINSite® group (p < 0.01) due to increased secretion and accumulation of fluid underneath this hydrocoloid cover. The minimal frequency of changes of this biological cover material brings a significant benefit to pediatric patients. CONCLUSION: Acellular pig dermis Xe-Derma® represents a reliable biological cover material. It is an advantageous alternative to synthetic temporary skin covers in the treatment of superficial scald burns in children.
Keywords: obvazy hydrokoloidní; Infant; Bandages, Hydrocolloid; Male; Skin; Body Surface Area; lidé; kůže; Humans; Child; Child, Preschool; biologické krytí; povrch těla; mužské pohlaví; kojenec; umělá kůže; dítě; Skin, Artificial; prospektivní studie; Biological Dressings; ženské pohlaví; Female; popálení; Burns; předškolní dítě; Prospective Studies